Non-profit Hospital Targeted Health Priorities and Collaboration With Local Health Departments in the First Round Post-ACA: A National Descriptive Study - Santos, Tatiane (Frontiers in Public Health, 2020)
We examined the community health needs assessments (CHNA) and implementation strategies of a national sample of 785 non-profit hospitals (NFPs) from the first round after the ACA. We found that the priorities targeted in the implementation strategies were well-aligned with the top community health priorities identified in CHNAs as reported in previous studies. The top five targeted priorities included obesity, access to care, diabetes, cancer, and mental health. We also found that 34% of sample NFPs collaborated with their local health department (LHD) to produce a single CHNA for their jurisdiction. Non-profit hospitals that collaborated with a LHD on the CHNA had higher odds of selecting behavioral health community issues (i.e., substance abuse, alcohol, and mental health), while hospitals located in counties with high uninsurance rates had lower odds of targeting these community issues. Our contribution was 3-fold; first, we examined a large sample of implementation strategies to extend on previous work that examined CHNAs only. This gives a more complete picture of which community issues identified in the CHNA are actually targeted for implementation. Second, this study was the first to present information on the status of NPF collaboration with LHDs to produce a single CHNA (from the NFP perspective). Third, we examined the association between targeted priorities with NFP and county-level characteristics. The community benefit requirement and Section 9007 of the ACA present an opportunity to nudge NFPs to improve the conditions for health in the communities they serve. The ACA has also challenged institutions in the health care sector to approach health through the social determinants of health framework. This framework moves beyond the provision of acute health services and emphasizes other inputs that improve population health. In this context, NFPs are particularly well-positioned to shift their contribution to improve population health beyond their four walls. Section 9007 is one mechanism to achieve such shift and has shown some promising changes among NFPs since its passage as reflected in the findings of this study. This study can inform future research related to NPF community benefit and local health planning.